Analisis Serangan dan Keamanan pada Denial of Service (DOS): Sebuah Review Sistematik - Covinia Dinda Berliana; Teguh Adi Saputra; indra gunawan (Jurusan Informatika STTR Cepu, 2022)
Threats or attacks on networks or information systems can cause misuse of information in organizational performance. One of the threats or attacks on network security or information systems is Denial of Service (DoS). The risk of losing information assets to the organization can occur if there are signs of adequate protection. Appropriate security technology can be set as anticipation and protection from DoS attacks, it is necessary to map in advance between the types of threats or attacks with existing security technologies based on the aspect of confidentiality. Fail2ban, Wireshark, SDMD, Intrusion Detection System (IDS), and Firewalls are the security technologies of choice in anticipating and protecting networks or information systems in security aspects.Denial of Service; Analisis; Review Sistematik